2003
DOI: 10.1029/2002jd002284
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of OBrO, IO, and OIO absorption signature in UV‐visible spectra measured at night and at sunrise by stratospheric balloon‐borne instruments

Abstract: [1] Absorption bands of OBrO, IO, and OIO in the visible region have been investigated in the data of the AMON (''Absorption par les Minoritaires Ozone et Nox'') and SALOMON (''Spectroscopie d'Absorption Lunaire pour l'Observation des Minoritaires Ozone et Nox'') balloon-borne spectrometers used to obtain measurements in the nighttime stratosphere, since 1992 and 1998 respectively. The absorption features initially detected in AMON residual spectra and attributed to OBrO are also observable in SALOMON data wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
4
12
0
Order By: Relevance
“…We find upper limits for the concentrations of both gases which put the strongest constraints on their abundance at the region in the Earth's atmosphere where tropospheric air enters the stratosphere to date. Our findings are consistent with previous studies that conclude undetectably low amounts of IO and OIO in the high-and mid-latitude stratosphere (e.g Wennberg et al, 1997;Pundt et al, 1998;Bösch et al, 2003;Berthet et al, 2003). We point out that the inferred upper limits for IO depend on the absorption cross section used for the spectral retrieval.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We find upper limits for the concentrations of both gases which put the strongest constraints on their abundance at the region in the Earth's atmosphere where tropospheric air enters the stratosphere to date. Our findings are consistent with previous studies that conclude undetectably low amounts of IO and OIO in the high-and mid-latitude stratosphere (e.g Wennberg et al, 1997;Pundt et al, 1998;Bösch et al, 2003;Berthet et al, 2003). We point out that the inferred upper limits for IO depend on the absorption cross section used for the spectral retrieval.…”
Section: Discussionsupporting
confidence: 82%
“…Murphy et al (1998), Murphy and Thomson (2000), and Murphy et al (2007) indeed found iodine in upper tropospheric and lower stratospheric particles. Most studies investigating the abundances of inorganic iodine species (IO and/or OIO) in the stratosphere conclude undetectably low amounts (Wennberg et al, 1997;Pundt et al, 1998;Bösch et al, 2003;Berthet et al, 2003). To date, the lowest estimate for the upper limit of the total gaseous inorganic iodine (I y ) burden in the high-and mid-latitude lower stratosphere is ∼0.1 ppt (Bösch et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ground-based observations in Arizona (United States) determined an upper limit for total inorganic iodine (I y ) of 0.2 pptv in the stratosphere [Wennberg et al, 1997]. Balloon-borne UV-Visible spectra derived lower stratospheric upper limits of around 0.1 pptv for both IO and OIO in the northern high and middle latitudes [Bösch et al, 2003], as well as over the tropics [Butz et al, 2009], consistent with previous reports. There is, however, one exception of a study reporting stratospheric IO mixing ratios of 0.65 and 0.8 pptv above Spitzbergen [Wittrock et al, 2000].…”
Section: Introductionsupporting
confidence: 71%
“…There have been several attempts to detect iodine oxides (IO and OIO) in the upper troposphere-lower stratosphere [Berthet et al, 2003;Bösch et al, 2003;Butz et al, 2009;Pundt et al, 1998;Wennberg et al, 1997;Wittrock et al, 2000]. Ground-based observations in Arizona (United States) determined an upper limit for total inorganic iodine (I y ) of 0.2 pptv in the stratosphere [Wennberg et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation